Olokizumab in patients with inflammatory phenotype of osteoarthritis, treatment experience - A. M. Lila; L. I. Alekseeva; E. A. Taskina; N. G. Kashevarova; E. P. Sharapova; E. A. Strebkova; N. M. Savushkina; A. R. Khalmetova; V. A. Nesterenko; A. S. Avdeeva; E. Yu. Samarkina; M. E. Diatroptov; et al. (Современная ревматология, 2024)
Objective: to investigate the efficacy and safety of olokizumab (OKZ) in patients with knee osteoarthritis (OA) with synovitis, persistent pain and ineffectiveness of previous conservative therapy.   Material and methods. The study included 15 patients with stage II–III knee OA who fulfilled the ACR criteria and had pain ≥50 mm on a visual analogue scale (VAS), synovitis and treatment failure. The age of patients ranged from 54 to 75 years; the duration of the disease was from 1 to 23 years. The duration of the study was 12 weeks, during which the patients received 3 subcutaneous injections of OKZ at a dose of 64 mg. The effectiveness of the treatment was assessed by the dynamics of pain intensity according to VAS, WOMAC and KOOS indices, the values of the DN4 questionnaire and the quality of life according to EQ-5D. In addition, the general assessment of the patient's health (GHA) according to VAS, the assessment of treatment efficacy by doctor and patient and the need for non-steroidal anti-inflammatory drugs (NSAIDs) were considered. All patients underwent laboratory testing.   Results and discussion. During treatment, there was a significant decrease in pain intensity according to VAS, a statistically significant improvement in the KOOS and WOMAC indices (p<0.05), quality of life according to the EQ-5D questionnaire and GHA. Patients and doctors rated the treatment results very positively: an improvement or significant improvement was observed in 92.3% of cases. Adverse events were identified in 4 patients, which in 2 cases served as the reason for discontinuation of OKZ treatment and termination of participation in the study. During treatment with OKZ, a statistically significant decrease in CRP and ESR values, an increase in the concentration of interleukin 6 (p = 0.003), COMP (p = 0.03) and PIINP (p = 0.01) were observed.   Conclusion. The results obtained suggest a significant symptomatic and anti-inflammatory effect of OKZ in patients with the inflammatory phenotype of OA.